Spin switching temperature modulated by the magnetic field and spontaneous exchange bias effect in single crystal SmFeO 3 - Ding, Shilei; Xue, Mingzhu; Liang, Zhongyu; Liu, Zhou; Li, Rubin; Cao, Shixun; Sun, Yunbin; Zhao, Jianjun; Yang, Wenyun; Yang, Jinbo (Journal of physics. Condensed matter, 2019)
The spin switching and exchange bias effect were investigated in the rare earth orthoferrite SmFeO composed of two antiferromagnetically coupled sublattices Sm and Fe with canted ferromagnetic moments and a temperature induced spin switching in single crystal SmFeO was observed. The spin switching temperature was found to be modulated by exerting different magnetic fields below the compensation temperature ([Formula: see text]). This effect could be explained as the changes of energy barrier related to the magnetization direction under different magnetic fields. In the meantime, the coercivity displayed strong dependence on the maximum applied magnetic fields in the hysteresis measurement. In addition, spontaneous exchange bias effect (EB) was observed with the largest EB field value of 1.2 T, and the EB field changed its sign across the compensation point. Our results indicate that the magnetic properties of SmFeO can be strongly affected and controlled by the temperature or the applied magnetic field during the measurement process, and it might lead to novel applications in magneto-optics, ultrafast switching, and magnetic sensing devices.